Civic engagement of Tengger indigenous community in strengthening ecological citizenship - Triyanto; Noventari, Widya; Mukhopadhyay, Tirtha Prasad; Maulana, Bariq; Anggraheni, Siska Fitri (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the involvement of the Tengger Indigenous People in strengthening ecological citizenship. Using a case study approach, this research examines how the values of Tri Hita Karana which emphasize harmony between humans and God (parahyangan), among fellow humans (pawongan), and with the environment (palemahan) support sustainable nature conservation practices. Data were collected through in-depth interviews, participatory observation, and documentation involving traditional leaders, community members, and key stakeholders in the Tengger region. The findings reveal that civic engagement rooted in local wisdom contributes to the preservation of natural resources such as water, reduces soil erosion, and promotes the sustainability of the Mount Bromo ecosystem. Moreover, collective community participation through traditional rituals such as Kasada and Entas-entas serves as a mechanism for fostering environmental awareness and strengthening social cohesion. These findings align with the theory of ecological citizenship, which posits that local community involvement in environmental stewardship is a critical factor in ensuring ecological sustainability. The study recommends the integration of local wisdom into sustainable conservation policies as an effective bottom-up approach.